Design and Establish of Prototype Triple-Function Bottle Closure Machine for Liquid foodstuff - วงศ์กระจ่าง, อนันต์; พูลสุขโข, ไพฑูรย์; คชฤทธิ์, นฤทธิ์ (Frontiers in Engineering Innovation Research, 2007)
Triple - Function closure bottle machine for liquid foodstuff was created by the competence of experts of the industrial bottle area. We have been starting point for the creation of successful solution, which are the new references on the market of packaging. The wide rang of Triple-Function bottle closure machine for liquid products permits to satisfy the most different production needs of customers. Triple-Function bottle closure machine is suitable for handling different kind of liquid products. Modern solution, advance technology, great reliability and convenience in operation are essential and characterizing features of machine. The prototype of machine is consisting of triple-function for pressing axial for three closure area of cork, maxi crown, and maxi cap. This machine force source froms the cylinder pneumatics system and it operate by the operator. The researcher also survey for the machine operator and the working environment. The results of this study showed that the machine can works according to the functions of the machine, and higher production rate than existent machine.